The Influence of Leadership Style and Work Environment on Employee Performance with Rewards as a Moderation Variable - Prananta, Kho Jessica Evania Falent (LifeSciFi, 2025)
Organizations increasingly face performance challenges marked by declining turnover and unmet performance targets, highlighting the need to better understand the factors that influence employee productivity. The objective is to analyze how leadership style and work environment impact employee performance and determine whether rewards moderate these relationships. Using a quantitative approach, the study employed census sampling of all 45 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The findings reveal that leadership style positively and significantly affects employee performance, while the work environment shows no significant direct effect. Importantly, rewards moderate both relationships, strengthening the influence of leadership style on performance and enhancing the work environment’s impact on performance. In conclusion, effective leadership combined with appropriate reward systems significantly drives employee performance, whereas environmental factors require reward mechanisms to become meaningful performance drivers. The study also contributes theoretically by confirming the role of rewards as a key moderator that strengthens leadership performance relationships. These findings imply that organizations should enhance leadership effectiveness and align reward systems to ensure work environment improvements translate into better employee performance.